# Solve for z 4-(2z-3)=3(z+2)+4 4-(2z-3)=3(z+2)+4
Simplify 4-(2z-3).
Simplify each term.
Apply the distributive property.
4-(2z)–3=3(z+2)+4
Multiply 2 by -1.
4-2z–3=3(z+2)+4
Multiply -1 by -3.
4-2z+3=3(z+2)+4
4-2z+3=3(z+2)+4
Add 4 and 3.
-2z+7=3(z+2)+4
-2z+7=3(z+2)+4
Simplify 3(z+2)+4.
Simplify each term.
Apply the distributive property.
-2z+7=3z+3⋅2+4
Multiply 3 by 2.
-2z+7=3z+6+4
-2z+7=3z+6+4
Add 6 and 4.
-2z+7=3z+10
-2z+7=3z+10
Move all terms containing z to the left side of the equation.
Subtract 3z from both sides of the equation.
-2z+7-3z=10
Subtract 3z from -2z.
-5z+7=10
-5z+7=10
Move all terms not containing z to the right side of the equation.
Subtract 7 from both sides of the equation.
-5z=10-7
Subtract 7 from 10.
-5z=3
-5z=3
Divide each term by -5 and simplify.
Divide each term in -5z=3 by -5.
-5z-5=3-5
Cancel the common factor of -5.
Cancel the common factor.
-5z-5=3-5
Divide z by 1.
z=3-5
z=3-5
Move the negative in front of the fraction.
z=-35
z=-35
The result can be shown in multiple forms.
Exact Form:
z=-35
Decimal Form:
z=-0.6
Solve for z 4-(2z-3)=3(z+2)+4

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top